2017
DOI: 10.1007/s12602-017-9253-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lactobacillus casei on DMH-Induced Colon Carcinogenesis in Mice

Abstract: The administration of probiotics is a promising approach to reduce the prevalence of colon cancer, a multifactorial disease, with hereditary factors, as well as environmental lifestyle-related risk factors. Biogenic polyamines, putrescine, spermidine, and spermine are small cationic molecules with great roles in cell proliferation and differentiation as well as regulation of gene expression. Ornithine decarboxylase is the first rate-limiting enzyme for polyamine synthesis, and upregulation of ornithine decarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…We also detected a tremendous expansion of the genus Lactobacillus , a member of the Bifico bacterial group. As reported by numerous studies, treatment with various strains of Lactobacillus reduces the severity of colitis and colitis‐associated carcinogenesis in both mice and humans Therefore, we assume that Lactobacillus is the crucial component in Bifico's chemoprevention of colitis‐associated tumorigenesis. Nevertheless, we did not detect any significant alteration in abundance of Bifidobacteria or Enterococcus , 2 other components in the Bifico cocktail, probably because we tested mucosa tissues rather than stool specimens, and the vast majority of the bacteria was excreted with feces.…”
Section: Discussionmentioning
confidence: 61%
“…We also detected a tremendous expansion of the genus Lactobacillus , a member of the Bifico bacterial group. As reported by numerous studies, treatment with various strains of Lactobacillus reduces the severity of colitis and colitis‐associated carcinogenesis in both mice and humans Therefore, we assume that Lactobacillus is the crucial component in Bifico's chemoprevention of colitis‐associated tumorigenesis. Nevertheless, we did not detect any significant alteration in abundance of Bifidobacteria or Enterococcus , 2 other components in the Bifico cocktail, probably because we tested mucosa tissues rather than stool specimens, and the vast majority of the bacteria was excreted with feces.…”
Section: Discussionmentioning
confidence: 61%
“…76 In addition, our results agree with the data obtained by Irecta-Nájera et al, 2017, as they showed in their study the protective effect of L. casei on DMH-treated mice. 78 Previous studies reported on the benecial effect of Turicibacter enrichment in the gut. Turicibacter has been correlated to the production of butyric acid, a short chain fatty acid, that act as an immunomodulators.…”
Section: Discussionmentioning
confidence: 99%
“…Lenoir et al [ 96 ] reported that, in C57BL/6 mice treated with DMH and Lactobacillus casei BL23, the secretion of cytokines was altered in response to probiotic administration and balanced Th17 responses emerged, culminating in the reduction of tumour incidence. L. casei ATCC 393 also delayed the onset of cancer, reduced the number of aberrant crypt foci [ 97 ], and modified pro-inflammatory cytokine levels in serum and T cell populations in the spleen [ 98 ] in DMH-induced colon carcinogenesis in mice. In addition, in a mouse model of azoxymethane (AOM) carcinogenesis, L. acidophilus reduced colonic lesions by 57%, and increased serum levels of IFN-γ and IL-10, as well as the number of circulating CD4+ and CD8+ T cells [ 99 ].…”
Section: Probiotic Intervention In the Positive Modulation Of Immumentioning
confidence: 99%